2014
DOI: 10.2139/ssrn.2376177
|View full text |Cite
|
Sign up to set email alerts
|

'Windfall Profits 2.0' During the Third Phase of the EU-ETS

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…In that case, the cleaner a technology is, the higher will be its marginal cost. As in Nicolai & Zamorano (2014) [16], assume that the unit cost of production and abatement for a firm i is equal to:…”
Section: Abatement Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the cleaner a technology is, the higher will be its marginal cost. As in Nicolai & Zamorano (2014) [16], assume that the unit cost of production and abatement for a firm i is equal to:…”
Section: Abatement Technologiesmentioning
confidence: 99%
“…Finally, extending the analysis to a market for permits covering several sectors, the paper assesses how different sectors are altered by the implementation of pollution permits. This is the first study in the literature, except Nicolai & Zamorano (2014) [16], to consider both several sectors and a percentage of reduction instead of fixing a pollution cap. It is found that the distribution of the emission reductions between sectors depends on the relative magnitude of both elasticities of demand and the ratios of marginal cost over emission intensity.…”
Section: Introductionmentioning
confidence: 99%
“…16 The cost parameter for abatement is determined by the inverse of the pollution factor solution, i.e., we fix γ according to the values observed from f The cement sector is the sector that proportionately reduces the output most while steel is the one that abates the most. Indeed, the lowest the cost over emission intensity ratio is that of cement while the three elasticities are quite close to each other.…”
Section: Illustration For Cement Electricity and Steel In The Eu-etsmentioning
confidence: 99%
“…This is the first study in the literature, except Nicolai & Zamorano (2014) [16], to consider both 5 several sectors and a percentage of reduction instead of fixing a pollution cap. It is found that the distribution of the emission reductions between sectors depends on the relative magnitude of both elasticities of demand and the ratios of marginal cost over emission intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation